2014
DOI: 10.1021/ma500273g
|View full text |Cite
|
Sign up to set email alerts
|

Folding Polymers with Pendant Hydrogen Bonding Motifs in Water: The Effect of Polymer Length and Concentration on the Shape and Size of Single-Chain Polymeric Nanoparticles

Abstract: A set of random copolymers based on a benzene-1,3,5-tricarboxamide functional methacrylate (BTAMA) and oligoethylene glycol methacrylate (oEGMA) with different degrees of polymerization (DP, from 110 to 450) and a 10 mol % loading of BTAMA were prepared using RAFT polymerizations. The pendant BTA units encode for the formation of helical aggregates via 3-fold hydrogen bonding while the oligoethylene glycol side chains provide solubility in water. The copolymers were characterized with size exclusion chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
104
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(126 citation statements)
references
References 65 publications
(47 reference statements)
16
104
0
2
Order By: Relevance
“…Continuing the study on this system 4 copolymers (10:90 BTAMA:oEGMA) (P1−P4) were synthesized with DPs from 110 to 461 to understand whether folding enforced by the BTA units is dependent on chain length. 226 The overall conclusion from this study was that the polymer initial size does not affect the folding process to a great extent, and all polymers behaved similar to those previously described. In a recent contribution, critical for the understanding of the folding process in the BTA systems, Hosono et al reported "soldiers−sergeant−soldiers" (S−S−S) experiments using SCNPs with a triblock architecture, 227 taking into account that just 5% of "sergeant" (with chiral side chains) free BTA units are required to induce full chiral amplification of achiral BTA stacks.…”
Section: Chemical Reviewssupporting
confidence: 79%
“…Continuing the study on this system 4 copolymers (10:90 BTAMA:oEGMA) (P1−P4) were synthesized with DPs from 110 to 461 to understand whether folding enforced by the BTA units is dependent on chain length. 226 The overall conclusion from this study was that the polymer initial size does not affect the folding process to a great extent, and all polymers behaved similar to those previously described. In a recent contribution, critical for the understanding of the folding process in the BTA systems, Hosono et al reported "soldiers−sergeant−soldiers" (S−S−S) experiments using SCNPs with a triblock architecture, 227 taking into account that just 5% of "sergeant" (with chiral side chains) free BTA units are required to induce full chiral amplification of achiral BTA stacks.…”
Section: Chemical Reviewssupporting
confidence: 79%
“…These studies reveal the potential of SCNPs but to mimic globular proteins, but the current state of the art is far from this goal. 69 Similarly shaped SCNPs were also visualized via TEM in recent work from our laboratory. 84 Cross-linking conditions typically involve dissolving the polymer in a good solvent, as poor solvation leads to aggregation.…”
Section: Characterizing the Morphology Of Scnpsmentioning
confidence: 96%
“…3). [2][3][4]6,69 Alternatively, the BTA unit can be attached to a polymer via azide-alkyne "click" chemistry. The authors refer to these SCNPs as "metastable" because when cast into a film, the polymers remain soluble in chloroform; however, upon heating, the SCNPs uncoil and the UPy moieties form interchain linkages resulting in an insoluble supramolecular network.…”
Section: Non-covalent Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, scattering techniques proved to be crucial to elucidate the single chain character in the BTA-based water-soluble systems. In recent studies, Gillissen et al combined spectroscopy and small-angle neutron scattering to unravel the relation between interchain self-assembly and the polymer conformation (39,44). For the first time, SANS experiments revealed the asymmetric shape of these SCPNs with a constant cross section, R cs , and variable length, L, with L > R cs (Figure 3).…”
Section: Characterization Of Dynamic Scpnsmentioning
confidence: 99%